The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1182/blood.2020008086
|View full text |Cite
|
Sign up to set email alerts
|

Postdischarge venous thromboembolism following hospital admission with COVID-19

Abstract: The association of severe COVID-19 with an increased risk of VTE has resulted in specific guidelines for its prevention and management. The VTE risk appears highest in those with critical care admission. The need for post discharge thromboprophylaxis remains controversial and this is reflected in the conflicting recommendations of expert guidelines. Our local protocol provides thromboprophylaxis to COVID-19 patients during admission only. We report post-discharge VTE data from an ongoing quality improvement pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
191
2
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(214 citation statements)
references
References 17 publications
(29 reference statements)
9
191
2
12
Order By: Relevance
“…Because we did not study a comparator group without COVID-19 but with other medical illness of similar severity, we were unable to determine the extent to which COVID-19 itself increases the risk of thromboembolic events. A U.K.-based study of 1,877 hospital discharges related to COVID-19 and 18,159 related to non-COVID-19 medical illness did not show a difference in the rate of hospitalization-associated VTE (OR: 1.6; 95% CI: 0.77 to 3.1) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because we did not study a comparator group without COVID-19 but with other medical illness of similar severity, we were unable to determine the extent to which COVID-19 itself increases the risk of thromboembolic events. A U.K.-based study of 1,877 hospital discharges related to COVID-19 and 18,159 related to non-COVID-19 medical illness did not show a difference in the rate of hospitalization-associated VTE (OR: 1.6; 95% CI: 0.77 to 3.1) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analyses tested whether the risk of VTE extends after the acute phase and, consequently, a post-discharge thromboprophylaxis may be recommended [ 12 , 13 ]. Our study, the largest to the best of our knowledge, confirmed that the rate of VTE appears low after hospital discharge, similar to other unselected populations of medically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of hospital charts integrated in an institutional quality program in London, the authors described a 0.5% rate of VTE within 42 days of hospital discharge [ 12 ]. In a retrospective cohort of 163 hospitalized patients, the 30-day post-discharge cumulative incidence of VTE was 0.6% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, Roberts et al. ( 5 ) found that post–hospital discharge–associated VTE rates for COVID-19 patients (4.8 per 1,000 hospital discharges) did not differ compared with 2019 pre-COVID-19 rates (3.1 per 1,000 hospital discharges; odds ratio: 1.6; 95% confidence interval: 0.77 to 3.1; p = 0.20). The PROTECT trial ( 6 ), published in 2011, compared prophylaxis with low-molecular-weight heparin to unfractionated heparin in 3,764 ICU patients.…”
mentioning
confidence: 96%
“…Proximal leg DVT was identified in 5.1% and 5.8% whereas PE rates were 1.3% and 2.3% for patients receiving dalteparin and unfractionated heparin, respectively. Additional pre-COVID-19 estimates of VTE rates from hospitalized patients in the ICU and ward setting have comparable frequencies ( Table 1 ) ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ). It would therefore appear that VTE rates reported in the current study are similar to expected rates for patients hospitalized without COVID-19.…”
mentioning
confidence: 99%